Evaluation of dentinogenesis inducer biomaterials: an in vivo study - Anabela B. Paula; Mafalda Laranjo; Carlos-Miguel Marto; Siri Paulo; Ana M. Abrantes; Bruno Fernandes; João Casalta-Lopes; Manuel Marques-Ferreira; Maria Filomena Botelho; Eunice Carrilho (University of São Paulo, 2019)
Abstract When exposure of the pulp to external environment occurs, reparative dentinogenesis can be induced by direct pulp capping to maintain pulp tissue vitality and function. These clinical situations require the use of materials that induce dentin repair and, subsequently, formation of a mineralized tissue. Objective: This work aims to assess the effect of tricalcium silicate cements and mineral trioxide aggregate cements, including repairing dentin formation and inflammatory reactions over time after pulp exposure in Wistar rats. Methodology: These two biomaterials were compared with positive control groups (open cavity with pulp tissue exposure) and negative control groups (no intervention). The evaluations were performed in three stages; three, seven and twenty-one days, and consisted of an imaging (nuclear medicine) and histological evaluation (H&E staining, immunohistochemistry and Alizarin Red S). Results: The therapeutic effect of these biomaterials was confirmed. Nuclear medicine evaluation demonstrated that the uptake of 99mTc-Hydroxymethylene diphosphonate (HMDP) showed no significant differences between the different experimental groups and the control, revealing the non-occurrence of differences in the phosphocalcium metabolism. The histological study demonstrated that in mineral trioxide aggregate therapies, the presence of moderate inflammatory infiltration was found after three days, decreasing during follow-ups. The formation of mineralized tissue was only verified at 21 days of follow-up. The tricalcium silicate therapies demonstrated the presence of a slight inflammatory infiltration on the third day, increasing throughout the follow-up. The formation of mineralized tissue was observed in the seventh follow-up day, increasing over time. Conclusions: The mineral trioxide aggregate (WhiteProRoot®MTA) and tricalcium silicate (Biodentine™) present slight and reversible inflammatory signs in the pulp tissue, with the formation of mineralized tissue. However, the exacerbated induction of mineralized tissue formation with the tricalcium silicate biomaterial may lead to the formation of pulp calcifications